Unprecedented hexagonal bipyramidal single-ion magnets based on metallacrowns. Issue 91 (27th October 2016) - Li, Quan-Wen; Wan, Rui-Chen; Chen, Yan-Cong; Liu, Jun-Liang; Wang, Long-Fei; Jia, Jian-Hua; Chilton, Nicholas F.; Tong, Ming-Liang
Abstract : Two novel Ln(iii ) (Ln = Ce or Nd) complexes based on [15-MC-6] (MC = metallacrown) and phosphine oxide are reported. Both of them feature a hexagonal bipyramidal LnO8 geometry ( D 6h ) and behave as single-ion magnets. Abstract : Two Ln(iii ) (Ln = Ce or Nd) complexes based on [15-MC-6] (MC = metallacrown) and phosphine oxide are reported for the first time with the Ln(iii ) ion featuring nearly perfect hexagonal bipyramidal LnO8 geometry, with pseudo- D 6h symmetry. Magnetic measurements reveal that both behave as single-ion magnets (SIMs), where the slow relaxation is dominated by the Raman mechanism.